Radiocarbon Dates from Late Neolithic and Early Bronze Age Settlements at Hemmed, Højgård and Trappendal, Jutland, Denmark - Lund, Kaare (Journal of Danish Archaeology, 1991)
Radiocarbon Dates from Late Neolithic and Early Bronze Age Settlements at Hemmed, Højgård and Trappendal, Jutland, Denmark